INTEGRATING RELIGIOUS EDUCATION INTO PUBLIC POLICY FOR SOCIAL INCLUSION: A COMPARATIVE ANALYSIS OF INDONESIA, CANADA, AND THE UNITED KINGDOM - Pratomo, Herdianto Wahyu (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: Religious education plays an essential role in shaping moral and ethical values in society. Its integration into public policy can serve as a strategic means to strengthen social inclusion, reduce discrimination, and enhance social cohesion. Purpose of the Study: This study examines how religious education contributes to public policy in fostering inclusive societies by comparing practices in Indonesia, Canada, and the United Kingdom. Methods: A qualitative comparative case study was conducted using literature A qualitative comparative case study was conducted through literature analysis, document review, and policy evaluation, drawing on constitutional mandates, curriculum frameworks, official reports, and scholarly research. Thematic analysis was used to compare how RE is institutionalized and its implications for inclusivity. Results: Canada and the UK demonstrate that inclusive and non-doctrinal RE—supported by pluralistic curricula and strong governance—effectively promotes tolerance, interfaith dialogue, and social cohesion. Indonesia continues to face fragmented systems and exclusive curricula, although initiatives such as pluralism-oriented curricula, interfaith programs, and Pancasila-based character education indicate emerging progress. Conclusions: Integrating RE into public policy can enhance inclusion when supported by targeted curriculum reform, teacher capacity-building, and accountability mechanisms. The study recommends cross-religious modules, multi-faith advisory councils, and inclusive pedagogies to strengthen the role of RE in building cohesive and democratic societies.